Pengembangan Media RatuChemWeb dalam Model Pembelajaran Flipped Classroom untuk Meningkatkan Motivasi dan Hasil Belajar Peserta Didik - Rahman, Andi Sriatu Nurdiyanti; Anwar, Muhammad; Wijaya, mohammad (Program Pasca Sarjana UNM, 2021)
This research is a development research that aims to develop RatuChemWeb in the Flipped Classroom learning model to increase students' motivation and learning outcomes on Acid and Base subject which is valid, practical, and effective to be used. The development model used in this study referred to Addie development model, which consisted of several stages, namely analysis, design, development, implementation, and evaluation. RatuChemWeb media that had been developed was conducted the validation stage by the validators/experts and had gone through trials and had been revised by developers to produce learning media which were valid, practical, and effective. The results show that the development of RatuChemWeb media have: (1) the media expert’s validation by 3.96 which is very valid criteria; (2) the material expert’s validation by 3.68 which is very valid criteria. The RatuChemWeb media is stated as practical due to the practicality test related to (1) its implementation in the Flipped Classroom learning model gains an average value of M = 1.98 with the category of being fully implemented, (2) the teacher's response is very positive with a percentage of 98.92% with very practical criteria, and (3) the students' responses are very positive with a percentage of 84.02% with very practical criteria. The media also meets the effective criteria with the results: (1) based on the Wilcoxon test, it obtains the significance value of p-value smaller than (0.000 < 0.05), which means there is a difference in the average students’ learning motivation before and after learning by using the RatuChemWeb media in the Flipped Classroom learning model with the increase of students' learning motivation from 60.83% to 74.72% and (2) the class completeness is 82% and the average value of N-Gain is 77% which is in high category.